Fibrotic injury after experimental deep vein thrombosis is determined by the mechanism of thrombogenesis - Henke, Peter K.; Varma, Manu R. V.; Moaveni, Daria K.; Dewyer, Nicholas A.; Moore, Andrea J.; Lynch, Erin M.; Longo, Christopher; Deatrick, Barry C.; Kunkel, Steven L.; Upchurch, Gilbert R., Jr.; Wakefield, Thomas W. (Thrombosis and Haemostasis, 2007)
Vessel wall matrix changes occur after injury, although this has not been well studied in the venous system. This study tested the hypothesis that the thrombus dictates the vein wall response and vein wall damage is directly related to the duration of thrombus contact. To determine the injury response over time, rats underwent inferior vena cava (IVC) ligation to produce a stasis thrombus, with harvest at various time points to 28 days (d). Significant vein wall matrix changes occurred with biomechanical injury (stiffness) peaking at 7–14 d, with concurrent early reduction in total collagen, an increase in early matrix metalloproteinase (MMP)-9 and late MMP-2, and concomitant increase in tumor necrosis factor (TNF)α, monocyte chemoattractant( MCP)-1 and tumor growth factor (TGF)β (all P <0.05). To isolate the effect of the thrombus and its mechanism of genesis, rats underwent 7 d or limited stasis (24 hours), non-stasis thrombosis, or non-thrombotic IVC occlusion (Silicone plug). Vein wall stiffness was increased seven-fold, with a five-fold reduction in collagen, and 5.5- to seven-fold increase in TNFα, MCP-1, and TGFβ with 7 d stasis as compared with controls (all P <0.05). By Picosirus red staining analysis, collagenolysis was significantly greater with 7 d stasis injury (P = 0.01) but neither MMP-9 nor MMP-2 activity correlated with injury mechanism. In addition, vein wall cellular proliferation and uPA gene expression paralled the stasis thrombotic injury. Limited stasis, non-stasis thrombosis and non-thrombotic IVC occlusion showed a lesser inflammatory response. These data suggest both a static component and the thrombus directs vein wall injury via multiple mechanisms.
Keywords: Veins; thrombosis; inflammation; collagen; vascular biology